Have we reached a tipping point? The mainstreaming of Euroscepticism in the UK. Issue 3 (June 2015) - Startin, Nicholas
Stephen George, the eminent scholar of the European Union, famously labelled the UK as the 'awkward partner' when analysing the country's relationship with the EU. The 'permissive consensus' evident in most EU nation states, at least prior to Maastricht and more recently the Eurozone crisis, was never 'clear-cut' in the UK. However, recent developments have propelled the issue of UK membership to the centre stage of British politics. By analysing some of the key historic variables which have contributed to the UK's ambivalence and hostility towards the EU as well as more recent factors such as Conservative Party splits over 'Europe' and the rise of UKIP, the article focuses on the role and influence of the tabloid press, and in particular the Daily Express, to demonstrate how the debate surrounding UK membership of the EU has completed its journey from the margins to the mainstream of British politics. It concludes that the lack of a 'level playing-field' in terms of EU coverage among the UK tabloid press has led to a situation where its citizens, in the context of an 'in-out' referendum, are unable to 'weigh up' the 'costs' and 'benefits' of EU membership in a rational and informed fashion.